An improved method for recursively computing upper bounds for two-colour Ramsey numbers - Kruger, Oliver (Utilitas Mathematica, 2020)
The two-colour Ramsey number R(m, n) is the least natural number p such that any graph of order p must contain either a clique of size m or an independent set of size n. We exhibit a method for computing upper bounds for /i(m,n) recursively, using known upper bounds of R(-, •) with lower values for at least one of the arguments. We also show how this method can be ised to improve many of the best known bounds that are available in the literature. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.